Notes on spiders of the genus Scytodes Latreille (Arachnida, Araneae, Scytodidae) from the Ferreira Penna Scientific Station, Pará, Brazil - Rheims, Cristina A.; Barreiros, José Augusto P.; Brescovit, Antonio D.; Bonaldo, Alexandre B. (Zootaxa, 2005)
Two new species of spiders of the genus Scytodes, Scytodes piyampisi and S. cotopitoka (Araneae, Scytodidae), are described from the Ferreira Penna Scientific Station, FLONA Caxiuanã, Melgaço, Pará, Brazil. The majority of the specimens were collected during structured inventories and natural history remarks on both new species are presented.